2002
DOI: 10.1063/1.1482137
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from open ended aluminum nitride nanotubes

Abstract: This letter reports the field emission measurements from the nanotubes of aluminum nitride which were synthesized by gas phase condensation using the solid-vapor equilibria. A dc arc plasma reactor was used for producing the vapors of aluminum in a reactive nitrogen atmosphere. Nanoparticles and nanotubes of aluminum nitride were first characterized by transmission electron microscope and tube dimensions were found to be varying from 30 to 200 nm in diameter and 500 to 700 nm in length. These tubes were mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
144
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(148 citation statements)
references
References 12 publications
2
144
1
1
Order By: Relevance
“…Motivated by interesting properties of SW(BN)NT and opto-electronic and field emitting properties of GaN and AlN tubular forms [21,25] we choose (8,0) AlP, GaAs and GaN single-wall nanotubes as prototype to investigate the stability and electronic properties of III-V compound nanotubes. Even if the single-wall nanotubes of these compounds have not been sythesized yet, the predictions of present work is essential for further efforts to achieve it.…”
Section: Single Wall Nanotubes Of Iii-v Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by interesting properties of SW(BN)NT and opto-electronic and field emitting properties of GaN and AlN tubular forms [21,25] we choose (8,0) AlP, GaAs and GaN single-wall nanotubes as prototype to investigate the stability and electronic properties of III-V compound nanotubes. Even if the single-wall nanotubes of these compounds have not been sythesized yet, the predictions of present work is essential for further efforts to achieve it.…”
Section: Single Wall Nanotubes Of Iii-v Compoundsmentioning
confidence: 99%
“…[17] Now, SWSiNTs are no longer hypothetical structures and it is not unrealistic to expect their fabrication with controllable size and diameter. Similarly, achievements of synthesis of singlewall BN nanotubes [18] and GaN [19,20], AlN [21] thickwall tubular forms has increased the interest in the theoretical analysis of compound nanotubes. [22,23,24,25] In addition, the synthesis of Mo and W chalcogenid nanotubes [26,27,28], and also NiCl tubular and cage structures have been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, aluminum nitride nanotubes (AlNNTs) which are neighbors of carbon in the periodic table have been an interesting subject of many studies [11,12]. After the prediction of AlNNTs by Zhang [13], Tondare et al [14], other articles reported the synthesis of AlNNTs through different methods [15,16]. AlNNTs is the largest band-gap semiconductors with the energy of 6.2 eV and have several unique properties such as high thermal conductivity, high electrical resistivity, low thermal expansion coefficient, high dielectric breakdown strength, good mechanical strength, excellent chemical stability, and non-toxicity [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…7 Owing to these very promising applications, significant research has been devoted to the synthesis of 1D-AlN nanostructures with various fabrication methods. These fabrication methods include metal organic vapour deposition, 8 arc discharging process, 9 chloride assisted growth, 10 carbothermal reduction, 11 gas reduction nitridation 12 and chemical vapour deposition (CVD). [13][14][15][16][17][18][19][20] Nevertheless, most of these fabrication methods involve the use of catalysts (mostly Au), which can introduce detrimental defects in AlN resulting poor performances in electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%